GITR ligation blocks allograft protection by induced CD25+CD4+ regulatory T cells without enhancing effector T-cell function. - Bushell, A; Wood, K (2007)
The induction of operational tolerance prior to transplant could provide a solution to the complications of current immunosuppression in transplantation. In rodents, operational tolerance frequently correlates with the presence of CD25(+)CD4(+) regulatory T cells (Tregs) but their function is usually demonstrated by adoptive transfer into lymphopenic hosts leading some to question their relevance to normal immunocompetent recipients. The role of these cells in primary transplant recipients has been explored using anti-CD25 antibody but specific targeting of Treg is not possible since CD25 is also up-regulated on activated effector T cells. To overcome this limitation we targeted the Treg associated molecule GITR in tolerized primary transplant recipients. This reverses regulation resulting in acute allograft rejection. This is not due to co-stimulation of effector cells since rejection mediated by isolated populations of CD4(+)CD25(-) or CD8(+)CD25(-) T cells transferred into Rag(-/-) mice was not enhanced by anti-GITR antibody. Furthermore, GITR cross-linking does not provide co-stimulation for in vitro proliferation of the same CD4(+)CD25(-) or CD8(+)CD25(-) T-cell populations in response donor-strain APC. Thus, CD4(+)CD25(+)GITR(+) Treg play an essential role in early graft protection in primary transplant recipients following tolerance induction providing further support for protocols that might generate similar populations in clinical transplantation.